Recent advances in designing and developing efficient sillenite-based materials for photocatalytic applications - Baaloudj, Oussama; Vu, Nhu-Nang; Assadi, Aymen Amin; Le, Van Quyet; Nguyen-Tri, Phuong (Advances in colloid and interface science, 2024)
Sillenite materials have been the subject of intense investigation for recent years due to their unique characteristics. They possess a distinct structure with space group I23, allowing them to exhibit distinctive features, such as an electronic structure ideal for certain applications such as photocatalysis. The present research delves into the structure, synthesis, and properties of sillenites, highlighting their suitability for photocatalysis. It explores also advanced engineering strategies for designing sillenite-based photocatalysts, including heterojunction formation, morphology modification, doping, and hybrid processes. Each strategy offers advantages and limitations that are critically discussed. The review then lists and discusses the photocatalytic performance of various sillenite-based systems recently developed for common applications, such as removing hazardous organic and inorganic contaminants, and even infrequent applications, such as microbial inactivation, H2 generation, CO2 reduction and N2 fixation. Finally, valuable insights and suggestions are put forward for future research directions in the field of sillenite-based photocatalysis. This comprehensive overview would provide a valuable resource for the development of efficient photocatalytic systems to address environmental and energy challenges. [Display omitted] •Recent concepts on various photocatalytic applications have been discussed.•Available synthesis techniques for sillenite materials have been covered.•The potential of sillenite crystals as photocatalysts has been explained.•Recent findings on using sillenite-based photocatalysts have been summarized.•Current approaches for enhancing the efficiency sillenites have been provided.